A Novel Approach Toward Q-Rung Orthopair Fuzzy Rough Dombi Aggregation Operators and Their Application to Decision-Making Problems - Saifullah Khan; Maaz Khan; Muhammad Sajjad Ali Khan; Saleem Abdullah; Faisal Khan (IEEE Access, 2023)
Since three way decision making is a better tool in order to deal with uncertain decision making problem. Therefore, in this paper a three way decision making approach is presented under q-rung orthopair fuzzy rough set environment. We first define some Dombi-operational laws for q-rung orthopair fuzzy rough set. Further, using the proposed operational laws some q-rung orthopair fuzzy rough Dombi aggregation operators namely, q-Rung Orthopair fuzzy rough Dombi weighted average (q-ROFRDWA) operator, q-Rung Orthopair fuzzy rough Dombi ordered weighted average (q-ROFRDOWA) operator and q-Rung Orthopair fuzzy rough Dombi hybrid weighted average (q-ROFRDHWA) operator are proposed. Also, some properties of the developed operators are investigated in details. Moreover, we present a three way decision making approach based on the developed aggregation operators with q-rung orthopair fuzzy rough set setting. Furthermore, a numerical example is presented for the effectiveness and application of the proposed method. Finally, a comparative study is conducted with other existing methods.